Obyczajowe, ale czy obyczajne. Wokół intymnych zapisków Stefana Żeromskiego - Kościewicz, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
Stefan Żeromski’s Journals focus mostly on matters of intellectual (books, theatre, and exhibition reviews, writing techniques) and personal character, with the latter including some very personal material. Żeromski was an exhibitionist in his writing. He described his autoerotic practices, his visits to brothels, details of sexual relationships with his mistresses as well as some personal problems of his friends and acquaintances. The present analysis of the writer’s Journals focusses on how Żeromski tended to write about his intimate life, what matters and to what extent they were treated as taboo by the author himself, by people from his closest environment, by readers of the manuscript version of his Journals, and finally, by editors and publishers of two 20th-century editions of his work. From this perspective, the close reading of Żeromski’s Journals will thus concentrate on issues such as private life, taboo, censorship and self-censorship.